Modelo de Lealtad a partir de un Análisis de Ecuaciones Estructurales (2016)
Day by day becomes more important for companies to own a database of loyal customers, because the continuous follow up and expanding business with them gives a bigger proﬁtability that getting new customers. Several methodologies have been used for satisfaction measure and loyalty of customers, most of them are based on Behavioural Psychology from positivist approach and leverages description of manifest behaviors measured directly and whose main objective is establish the direct importance that each service driver has about loyalty, as in case of methodologies based on regression models. In this paper I illustrate an application of a Loyalty Model that looking for through an analysis of Structural Equation Modeling with latent variables, deﬁne the size of eﬀect on the loyalty for phenomena like overall satisfaction with service, repurchase intention and recommendation.